GAS BIO DARI HASIL FERMENTASI ECENG GONDOK DUA FASE DAN KAYU LAMTORO SEBAGAI DAHAN BAKAR UNTUK MEMASAK - Tjutju Nurhayati (Jurnal Penelitian Hasil Hutan, 1994)
Riogas of 2-phase water hyacinth fermentation  and lamtoro wood of 4 years old were used as fuel for  cooking by the family.  The value of nutrition requirement was  10,353 calories  made of rice, meat,  fermented  soyabean,  etc. consumed by 5 persons in the family.The  study revealed that bio gas consumptian  was 1.281 1.  with the caloriffic  value of  4,569 Kcal/m3  and methane  content of 46.78%. This bio gas energy  was  5.85 Mcal for  181 minutes of cooking period.  This bio  gas consumption can be fulfilled  by using  33.14 kg fresh Water hyacinth per day in 300 1 volume reactor and 4.3% dry Water.Lamtoro  consumption  Was  4, 243 g for  159  minutes of cooking period with the  caloriffic  vatue of  4,299 Kca/kg and moisture  content of 14.50%. This lamtoro enetgy  was   18.24 Meal per day per family.  The total weight of wood cutting was   164. 80 kg with the moisture content ranged from  44. 74 to 63.33  %.  This  amount  will  be  enough for  cooking for  3 4 days  when converted  to 14.50 % maisture  content.